Perancangan Keamanan Internet Jaringan Hotspot Mikrotik pada Winbox dan Wireshark - Rahmat Novrianda Dasmen; Abdur Rohman Syarif; Heru Saputra; Rahmat Amrullah (DoubleClick: Journal of Computer and Information Technology, 2022)
Mikrotik, a technology that provides Internet services by turning computers into network routers. The computer network of SMA Negeri 16 Palembang uses a traditional cable network with star type. In this research, the process of designing a network using Mikrotik and managing and distributing bandwidth as needed at SMA Negeri 16 Palembang is carried out using the Network Development Life Cycle (NDLC) model. The result of this research is that Mikrotik can manage all computer networks. In the distribution of bandwidth regularly on the proxy can provide efficiency over the use of the internet. Mikrotik can maximize network usage if the overall bandwidth has been set. Keywords: Mikrotik, Computer Network, Router and Type Network